Implementation of Information System (Loyverse and QRIS) to Increase Sales in TP Collection MSMEs Pangandaran - Nurul Mardhiah Sitio*; Sari Usih Natari; Prilia Salsabila; Teguh Putra Mahali (Universitas Syiah Kuala, 2023)
This study aims to describe the application of Loyverse and QRIS applications for financial management and inventory management. The object of this research is the UMKM Teguh Putra Collection which is located in Pangandaran District, Pangandaran Regency.This research uses a qualitative method with a descriptive approach. The results of this study show that the Loyverse and QRIS applications are proven to help financial management and inventory management. The Loyverse application helps in recording purchases,inventory data, financial reports, inventory reports, and others. The addition of QRIS helps businesses to accommodate buyers who want t o buy products with cashless payments. From the description above, it is concluded that the application of Loyverse and QRIS is beneficial to the store's information system because the management is more organized and more efficient and effective. From the analysis of implementation, it is concluded that the application of Loyverse and QRIS is beneficial to the store's information system because the management is more organized and more efficient and effective.